2015
DOI: 10.1016/j.jnucmat.2014.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Defect kinetics and resistance to amorphization in zirconium carbide

Abstract: To better understand the radiation response of zirconium carbide (ZrC), and in particular its excellent resistance to amorphization, we have used density functional theory methods to study the kinetics of point defects in ZrC. The migration barriers and recombination barriers of the simple point defects are calculated using the ab initio molecular dynamics simulation and the nudged elastic band method. These barriers are used to estimate C and Zr interstitial and vacancy diffusion and Frenkel pair recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…as reported by Zheng, et al [22], are quite high and would not activate in the temperature range studied. Furthermore, the antisite defect energy is very high (greater than 11 eV [26]) so that the C and Zr sub-lattices are essentially independent of each other.…”
Section: Thickness Dependence Of Irradiated Microstructuresupporting
confidence: 49%
See 2 more Smart Citations
“…as reported by Zheng, et al [22], are quite high and would not activate in the temperature range studied. Furthermore, the antisite defect energy is very high (greater than 11 eV [26]) so that the C and Zr sub-lattices are essentially independent of each other.…”
Section: Thickness Dependence Of Irradiated Microstructuresupporting
confidence: 49%
“…We can infer the processes involved in the thermally activated defect growth regime. Because calculations of defect migration energies have shown that there are high barriers to migration for both carbon and zirconium vacancies [22], these defects would not be mobile at the temperatures used in these experiments. Since this means that vacancies cannot agglomerate, this explains why no voids were observed in this study as there would be no mechanism for void growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the radiation responses of ZrC are still poorly understood, including both its high-temperature microstructural changes [4] and the origin of its superior resistance to amorphization. In fact, radiation-induced amorphization of ZrC has not yet been observed experimentally at any temperature or dose [1, [4][5][6][7][8][9][10]. One of the key unknown parameters needed to model the irradiation response of ZrC, e.g., using SRIM simulations [11], is the threshold displacement energy (E d ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the low value along the [111] direction can be explained by the fact that when the C PKA was displaced along this direction it moves into a region of significant open space and rapidly begins to form bonds with the second nearest-neighbor C atoms before PKA kicks out its second nearest neighbor C atom along the [011] direction, the C PKA goes back to its original lattice site, and the kicked-out C atom forms a C-C dumbbell with the sixth nearest neighbor C atom of the original PKA site. Along the Zr Frenkel pairs are formed at the end of the MD simulation, presumably in part due to the fact that the C PKA is displaced most dramatically, and perhaps in part due to the much lower formation energies of C Frenkel pairs than Zr ones[3,7]. The C Frenkel pairs at the end of MD runs are fully relaxed to obtain their stable configuration.…”
mentioning
confidence: 99%